Spatial market efficiency of grain markets in the post-Soviet countries and implications for global food security - Miranda Svanidze (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2020)
This doctoral thesis studies the spatial market efficiency of wheat markets in selected post-Soviet countries; particularly in Russia, the largest wheat exporting country in the world, and in the grain import-dependent countries of Central Asia and the South Caucasus. Increased grain production in the Black Sea region, and in Russia specifically, is crucial for meeting increasing global agricultural demand and global food security. Grain production in Russia could be boosted by increasing grain production efficiency and also by re-cultivating formerly abandoned agricultural land. However, to increase Russia's role in global wheat supply, additional grain production potential has to coincide with improving the country's grain export perspectives. On the other hand, the realization of Russia's export capacity largely depends on the performance of its regional grain markets domestically. Using price transmission and panel data analyses in a comparative context, this study finds the wheat market of Russia segmented, with the primary wheat export region poorly integrated into the domestic market. This thesis also demonstrates that regional wheat market integration in Russia is relatively low and heterogeneous and trade costs are relatively high compared to the USA, mostly due to large distances between grain producing regions. In addition, by including the USA as benchmark country, a comparative approach enables a more comprehensive assessment of the spatial market efficiency of the wheat market in Russia. The results also provide evidence on the dissimilarity of the underlying fundamental mechanism of market integration between Russia and the USA. In Russia, the physical trade of wheat mainly fosters market integration at the interregional level, whereas in the USA, in addition to physical trade, information flows induced by commodity futures markets play a major role in the regional grain market integration. (...) – – Diese Arbeit untersucht die räumliche Markteffizienz von Getreidemärkten in ausgewählten Ländern der ehemaligen Sowjetunion, insbesondere Russland, dem größten Getreideexportland weltweit, sowie in vom Getreideimport abhängigen Ländern Zentralasiens und des Südkaukasus. Die erhöhte Getreideproduktion in der Schwarzmeerregion, und in Russland speziell, spielt eine entscheidende Rolle, um den wachsenden weltweiten Bedarf an Agrarprodukten und dem Problem der Ernährungssicherheit zu begegnen. Damit Russland einerseits seine Rolle in der globalen Weizenproduktion jedoch ausfüllen kann, ist die Mobilisierung zusätzlicher Produktionspotenziale zusammen mit einer Verbesserung der Exportmöglichkeiten für Getreide notwendig. Andererseits hängt die Ausschöpfung der Exportmöglichkeiten entscheidend von den inländischen regionalen Getreidemärkten ab. Auf der Grundlage von Preistransmissions- und Paneldatenuntersuchung in einem vergleichenden Kontext wird in dieser Studie festgestellt, dass der Weizenmarkt Russlands segmentiert ist und die primäre Getreide-Exportregion schwach in den Inlandsmarkt integriert ist. Diese Arbeit zeigt auch, dass die regionale Integration des Weizenmarktes in Russland teilweise relativ gering ist und die Handelskosten im Vergleich zu den USA relativ hoch sind, was vor allem auf große Entfernungen zwischen den Getreide produzierenden Regionen zurückzuführen ist. Darüber hinaus ermöglicht ein vergleichender Ansatz durch die Einbeziehung der USA eine umfassendere Bewertung der räumlichen Effizienz des Weizenmarktes in Russland. Die Ergebnisse liefern auch Hinweise auf die Unterschiede des zugrunde liegenden grundlegenden Mechanismus der Marktintegration zwischen Russland und den USA. In Russland fördert der physische Handel mit Weizen hauptsächlich die Marktintegration auf interregionaler Ebene, während in den USA neben dem physischen Handel auch die von den Warenterminmärkten induzierten Informationsflüsse eine wichtige Rolle bei der regionalen Integration der Getreidemärkte spielen. (...)
urn:nbn:de:gbv:3:2-130300
Keywords: 330; Getreidemarkt; Effizienzmarkthypothese; Ernährungssicherung; Landwirtschaftliche Entwicklung; Osteuropa